Gas-phase detection methods using diode lasers - Baran, S; Stuart Baran (2009)
Diode lasers are a convenient and economical source of near-infrared radiation, which may usefully be applied to a host of diﬀerent sensitive detection methods; this thesis presents novel extensions of these methods, making use of the favourable characteristics of this type of light source. The ﬁrst part of this thesis details the development of an optical feedback cavity-enhanced absorption spectroscopy (OF-CEAS) apparatus, including the development of the optical system, the sample handling, and the electronics for feedback phase control. A preliminary demonstration of the system is reported, presenting the detection of atmospheric water absorptions close to 1596 nm. Optimisation and application of the OF-CEAS spectrometer are then demonstrated, after which the spectrometer is applied to the sensitive detection of carbon dioxide absorptions suitable as a diagnostic aid in identifying Heliobacter pylori infection. A time-normalised α-min value of 5.8 × 10−9 cm−1s1/2 was measured for these spectra. Further optimisation of the system leads to an ultimate detection sensitivity of 1.42 × 10−9 cm−1s1/2, measured on absorption transitions in acetylene close to 1532 nm. In order further to characterise the performance of the OF-CEAS system, analogous experiments are presented using the OF-CEAS setup and a standard diode-laser cavity-enhanced absorption spectroscopy (CEAS) apparatus. Detection is carried out on the P(6) line of the ν1 + ν3 vibrational band of the mixed isotopologue of acetylene, 12-C13-CH2. Direct comparison is made between the sensitivities of the two methods, and in light of this the suitability of each technique for detection in diﬀerent environments is considered. The well-characterised and consistent frequency scale which is inherent to the OF-CEAS technique is then applied to a line shape analysis for the presented absorption spectra. Pressure-broadening coeﬃcients are determined for selected absorptions in the ν1 + ν3 band of acetylene. In spite of the low resolution associated with this technique, this accurate frequency scaling allows observation of subtle line shape eﬀects such as Dicke collisional narrowing using the data presented in Chapter 3 for the R(60) line in the 3ν1 + ν3 vibrational band of CO2. These eﬀects are quantiﬁed through use of a Galatry ﬁt to each absorption spectrum. The statistical signiﬁcance associated with the use of such a model, and the physical meaning of the results, are examined and discussed. An alternative strategy for increasing the sensitivity of a diode-laser-based gas monitoring technique lies in moving detection to the mid-infrared region, where the absorption cross-sections are generally larger. With this motivation, diﬀerence frequency generation is presented, to produce radiation close to 3.5 µm which is then applied to a series of diﬀerent enhanced spectroscopy techniques. The optimal sensitivity, of 32 ppb NO2 at 45 Torr total sample pressure, was achieved using wavelength modulation spectroscopy. The diﬀerent techniques are compared and possible improvements to them are put forward. Finally, proof-of-principle work is presented seeking to combine the enhanced circulating power associated with the optical-feedback-locked techniques and non-linear optical techniques to move detection to a more favourable spectral region. Light close to 429 nm is generated by second harmonic generation in a crystal of potassium niobate, with resonance-enhancement aﬀorded by a feedback V-cavity of the sort employed in OF-CEAS. The potential of such a system for diode-laser-based generation of blue and ultraviolet light is demonstrated and discussed, along with improvements that might be implemented to increase the eﬃciency of the system.